Acknowledgement of emotional facial expression in Mexican college students - Bilbao, María de los Ángeles (2007)
The aim of this study is to explore the patterns of emotion recognition in Mexican bilinguals using the JACFEE (Matsumoto & Ekman, 1988). Previous cross cultural research has documented high agreement in judgments of facial expressions of emotion, however, none of the previous studies has included data from Mexican culture. Participants were 229 Mexican college students (mean age 21.79). Results indicate that each of the seven universal emotions: anger, contempt, disgust, fear, happiness, sadness and surprise was recognized by the participants above chance levels (p < .001), regardless of the gender or ethnicity of the posers. These findings replicate reported data on the high cross cultural agreement in emo- tion recognition (Ekman, 1994) and contribute to the increasing body of evidence regardingthe universality of emotions.